2018
DOI: 10.1136/emermed-2017-207211
|View full text |Cite
|
Sign up to set email alerts
|

Development of sustainable community paramedicine programmes: a case study in Pennsylvania

Abstract: The challenges and solutions from the four programmes under study can provide a road map for the development of CP programmes for other communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Respecto a estrategias orientadas a la ampliación de cobertura, mejoramiento del servicio y sostenibilidad de los sistemas de salud, la literatura al respecto presenta entre otras opciones la consideración de programas de paramédicos en comunidades rurales y urbanas como soporte a la ges�ón de las ESE, en ese sen�do, los estudios realizados iden�fican la fac�bilidad a nivel de costo-efec�vidad donde es ideal la consideración de un marco metodológico transformador para la sostenibilidad que podría ser extrapolado a los diferentes programas propuestos en las ESE para la op�mización de la opera�vidad. (Huang et al, 2018). Adicionalmente, se iden�ficó la aplicación de la gerencia de valor que según Rojas(2016), �ene el obje�vo de "conservar en términos de saneamiento fiscal, estabilidad financiera, un adecuado control y manejo del presupuesto, las finanzas y el patrimonio público" (pág.…”
Section: Marco Teóricounclassified
“…Respecto a estrategias orientadas a la ampliación de cobertura, mejoramiento del servicio y sostenibilidad de los sistemas de salud, la literatura al respecto presenta entre otras opciones la consideración de programas de paramédicos en comunidades rurales y urbanas como soporte a la ges�ón de las ESE, en ese sen�do, los estudios realizados iden�fican la fac�bilidad a nivel de costo-efec�vidad donde es ideal la consideración de un marco metodológico transformador para la sostenibilidad que podría ser extrapolado a los diferentes programas propuestos en las ESE para la op�mización de la opera�vidad. (Huang et al, 2018). Adicionalmente, se iden�ficó la aplicación de la gerencia de valor que según Rojas(2016), �ene el obje�vo de "conservar en términos de saneamiento fiscal, estabilidad financiera, un adecuado control y manejo del presupuesto, las finanzas y el patrimonio público" (pág.…”
Section: Marco Teóricounclassified
“…Paramedicine represents a unique intersection of health care, public health, and public safety and allows paramedics and emergency medical technicians (EMTs) to operate in expanded roles by assisting with primary healthcare, preventive services and public health for underserved populations in the community. It has been deployed in a variety of settings, 3 including illness management, 4 senior housing, 5,6 flood disaster, 7 rural communities, 8,9 and recently in a ED-to-home transition intervention. 10 There is a push to study the effectiveness of these programs in achieving the IHI (Institute for Healthcare Improvement) Triple Aim.…”
Section: Management Of Frequent Ed Users By Community Paramedics Imprmentioning
confidence: 99%
“…10 There is a push to study the effectiveness of these programs in achieving the IHI (Institute for Healthcare Improvement) Triple Aim. 11,12 In general, there is a dearth of scholarly literature evaluating CP programs 3,13,14 related to program implementation, patient care and experience, and economic impact. 15,16 Based on extensive literature review by the authors, no study has reported the frequency and modality of CP interventions to patients in the program, nor described the process of enrollee intake and assessments.…”
Section: Management Of Frequent Ed Users By Community Paramedics Imprmentioning
confidence: 99%
“…This includes programs in support of preventative services, care for patients with chronic illness, patients determined to be high utilizers, care for patients after being discharged from the hospital, and to develop social support networks. [55][56][57][58][59] Most CP/MIHC programs in the United States were born out of the need to provide…”
Section: Community Paramedicinementioning
confidence: 99%